Deoxygenation of waste cooking oil and non-edible oil for the production of liquid hydrocarbon biofuels. (January 2016) - Romero, M.J.A.; Pizzi, A.; Toscano, G.; Busca, G.; Bosio, B.; Arato, E.
Highlights: Deoxygenation of waste cooking oil and Jatropha oil. Testing of hydrotalcite and CaO as catalysts in a free hydrogen atmosphere. Evaluation of the process in batch setup and semi-batch setup. Production of liquid biofuels composed mostly of hydrocarbons. Abstract: Deoxygenation of waste cooking vegetable oil and Jatropha curcas oil under nitrogen atmosphere was performed in batch and semi-batch experiments using CaO and treated hydrotalcite (MG70) as catalysts at 400 °C. In batch conditions a single liquid fraction (with yields greater than 80 wt.%) was produced containing a high proportion of hydrocarbons (83%). In semi-batch conditions two liquid fractions (separated by a distillation step) were obtained: a light fraction and an intermediate fraction containing amounts of hydrocarbons between 72–80% and 85–88% respectively. In order to assess the possible use of the liquid products as alternative fuels a complete chemical characterization and measurement of their properties were carried out.